Behaviour of corroded shear-critical reinforced concrete beams repaired with NSM CFRP rods. (May 2015) - Almassri, Belal; Kreit, Amjad; Al Mahmoud, Firas; Francois, Raoul
Abstract: This paper discusses the results of an experimental program designed to investigate the effect of repairing the RC corroded shear-critical deep beams with near surface mounted (NSM) carbon fibre-reinforced polymer (CFRP) rods. A 28-year-old RC beam corroded by exposure to a chloride environment was cut into two small short-shear-span beams, along with a control beam of the same characteristics (age, length and cross-section). One RC corroded deep beam was repaired in bending and the other one was repaired in both bending and shear with NSM CFRP rods. Force–displacement curves were plotted for the corroded and control beams. After the beams had been tested up to failure, the loss of mass was measured and plotted for both the longitudinal and transverse reinforcement. The slip of tensile reinforcement at the end of the beams was also measured during the tests. Experimental results show that both corroded and control deep beams repaired only in bending failed due to shear mode of failure (diagonal tension failure), while corroded and control beams repaired in both bending and shear failed due to concrete crushing. The test results also showed that the corrosion of both longitudinal and transversal reinforcement hardly modified the mechanical response of deep beams.